Influenza A virus-derived siRNAs increase in the absence of NS1 yet fail to inhibit virus replication - Tsai, Kevin (RNA, 2018)
While the issue of whether RNA interference (RNAi) ever forms part of the antiviral innate immune response in mammalian somatic cells remains controversial, there is considerable evidence demonstrating that few, if any, viral small interfering RNAs (siRNAs) are produced in infected cells. Moreover, inhibition of RNAi by mutational inactivation of key RNAi factors, such as Dicer or Argonaute 2, fails to enhance virus replication. One potential explanation for this lack of inhibitory effect is that mammalian viruses encode viral suppressors of RNAi (VSRs) that are so effective that viral siRNAs are not produced in infected cells. Indeed, a number of mammalian VSRs have been described, of which the most prominent is the influenza A virus (IAV) NS1 protein, which has not only been reported to inhibit RNAi in plants and insects but also to prevent the production of viral siRNAs in IAV-infected human cells. Here, we confirm that an IAV mutant lacking NS1 indeed differs from wild-type IAV in that it induces the production of readily detectable levels of Dicer-dependent viral siRNAs in infected human cells. However, we also demonstrate that these siRNAs have little if any inhibitory effect on IAV gene expression. This is likely due, at least in part, to their inefficient loading into RNA-induced silencing complexes.